The effect of camelina oil on vascular function in essential hypertensive patients with metabolic syndrome: a randomized, placebo-controlled, double-blind study. Issue 3 (15th November 2021) - Bellien, Jeremy; Bozec, Erwan; Bounoure, Frédéric; Khettab, Hakim; Malloizel-Delaunay, Julie; Skiba, Mohamed; Iacob, Michèle; Donnadieu, Nathalie; Coquard, Aude; Morio, Béatrice; Laillet, Brigitte; Rigaudière, Jean-Paul; et al.
ABSTRACT: Background: The effects of a dietary supplementation with the vegetable ω-3 α-linolenic acid (ALA) on cardiovascular homeostasis are unclear. In this context, it would be interesting to assess the effects of camelina oil. Objective: This study aimed to assess the cardiovascular and metabolic effects of camelina oil in hypertensive patients with metabolic syndrome. Methods: In a double-blind, placebo-controlled randomized study, treated essential hypertensive patients with metabolic syndrome received, during 6 mo, either cyclodextrin-complexed camelina oil containing ≈ 1.5 g ALA/d ( n  = 40) or an isocaloric placebo ( n  = 41), consisting of the same quantity of cyclodextrins and wheat starch. Anthropometric data, plasma lipids, glycemia, insulinemia, creatininemia, TBARs, high-sensitivity C-reactive protein, and n–3, n–6, and n–9 fatty acids in erythrocyte membranes were measured. Peripheral and central blood pressures, arterial stiffness, carotid intima-media thickness, and brachial artery endothelium-dependent flow-mediated dilatation (FMD) and endothelium-independent dilatation were assessed. Results: Compared with placebo, camelina oil increased ALA (mean ± SD: 0 ± 0.04 compared with 0.08 ± 0.06%, P  <0.001), its elongation product EPA (0 ± 0.5 compared with 0.16 ± 0.65%, P  <0.05), and the n–9 gondoic acid (GA; 0 ± 0.04 compared with 0.08 ± 0.04%, P  <0.001). No between-group difference was observed for cardiovascular parameters. However, changes in FMD were associated with the magnitude of changes in EPA (r = 0.26, P  = 0.03). Compared with placebo, camelina oil increased fasting glycemia (–0.2 ± 0.6 compared with 0.3 ± 0.5 mmol/L, P  <0.001) and HOMA-IR index (–0.8 ± 2.5 compared with 0.5 ± 0.9, P  <0.01), without affecting plasma lipids, or inflammatory and oxidative stress markers. Changes in HOMA-IR index were correlated with the magnitude of changes in GA (r = 0.32, P  <0.01). Nutritional intake remained similar between groups. Conclusion: ALA supplementation with camelina oil did not improve vascular function but adversely affected glucose metabolism in hypertensive patients with metabolic syndrome. Whether this adverse effect on insulin sensitivity is related to GA enrichment, remains to be elucidated.